Relasi Adat dan Islam dalam Ritual Sumpah Garap Sebagai Alternatif Penyelesaian Tindak Pidana Pencurian pada Masyarakat Islam Sasak - Mulhimmah, Baiq Ratna; Jalilah, Nisfawati Laili (TAJDID, 2021)
Garap is a ritual that is believed by the Sasak Islamic community in the southern part of Lombok as an alternative to the settlement of the crime of theft. This ritual is carried out since the death of the Nyatok Guardian. This research aims to describe the meaning of garap for the Sasak Islamic community, the reason the garap tradition is able to become the main mechanism for resolving criminal acts, explain the position of garap as the settlement of criminal acts informal law and describe the relationship between adat and Islam in the Garap process. The method used is descriptive qualitative research using a legal anthropological approach. Data mining using observation, interviews, and documentation. The results show that the garap ritual has a very important meaning, in terms of function, it is not only used as a mechanism for resolving cases of theft an sich, but also as a guardian of a village community order. Work on as an alternative to resolving disputes over its position via vis with state law. The thick culture and the strength of the community in holding religious teachings make the garap ritual inseparable from the influence of religion (belief) so that the relationship of religious customs can be seen from the process of working on rituals such as reading the holy verses of the Qur'an in the process of the cultivation path.